SOCIIAL-PHILOSOPHICAL SIGNIFICANCE OF INFORMATION SYSTEM IN KAZAKHSTAN (Journal of Philosophy, Culture and Political Science, 2022)
Abstract. Technological basis for the formation of the information space of modern society is information and communication technologies. These are computers, computer networks, the internet, communication tools, information resources in electronic media, and much more. The combination of these components has a significant resource in the information society. Therefore we are searching for an answer to the role of information space in social philosophy.Nowadays, the information space of Kazakhstan reflects the ways to achieve a high level of well-being of the population with new developed and accessible, innovative and information technologies. The article deals with the process of informatization of Kazakhstan's information space in all spheres of society. In addition, the article discusses the problems and advantages in the field of informatization in Kazakhstan, information security, useful and useless aspects of the social network in society, ways of digitalization of the state, social and philosophical aspects.Key words: information space, information society, philosophy, philosophy of time, digital Kazakhstan, e-government